Pengaruh Gaya Kepemimpinan, Kompensasi, Dan Lingkungan Kerja Terhadap Loyalitas Karyawan (Studi pada PT Albarokah Makmur Jaya. Lumajang) - Popi Dwi Wulandari; Abdul Kodir Djaelani; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of leadership style, compensation, and work environment on employee loyalty at PT Albarokah Makmur Jaya, Kunir, Lumajang. A quantitative approach was employed by distributing questionnaires to all employees, totaling 35 respondents, using a saturated sampling technique (census). The variables examined leadership style, compensation, and work environment are key factors in measuring the level of employee loyalty. The findings of this research demonstrate that simultaneously, leadership style, compensation, and work environment have an effect on employee loyalty. Partially, leadership style does not influence employee loyalty, compensation does not influence employee loyalty, while the work environment has a partial influence on employee loyalty. This study suggests that the company needs to improve the quality of its leadership style, enhance its compensation system, and maintain as well as develop a conducive work environment to strengthen employee loyalty and minimize turnover in the future. Keywords: Leadership Style, Compensation, Work Environment, Employee Loyalty.